Deuterium gas puff Z-pinch at currents of 2 to 3 mega-ampere; Physics of Plasmas; Vol. 19, iss. 3 - Klir D.; Shishlov A. V.; Kubes P.; Rezac K.; Fursov F. I.; Kokshenev V. A.; Kovalchuk B. M.; Kravarik J.; Labetsky A. Yu.; Ratakhin N. A. Nikolay Aleksandrovich (2012, 2012)
Title screen